2016
DOI: 10.4028/www.scientific.net/amr.1140.221
|View full text |Cite
|
Sign up to set email alerts
|

Quick Stop Device to Analyze the Chip Formation Mechanisms in Face Grinding

Abstract: The chip formation mechanisms during grinding are not yet fully understood. The abrupt interruption of the grinding process with a quick stop device is a suitable method to analyze the chip formation mechanisms during grinding. However, there is no device available that enables a reproducible interruption at cutting speeds above vc = 5 m/s. Therefore a new method for the interruption of face grinding processes in order to analyze the chip formation mechanisms is presented in this paper. A quick stop device is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This enables the interruption of grinding process with cutting speeds of up to 50 m/s. This means an increase of 43% of the cutting speed which can be interrupted with this device, compared with previously used devices [44,45,49,50].…”
Section: Quick-stop Devicementioning
confidence: 84%
See 1 more Smart Citation
“…This enables the interruption of grinding process with cutting speeds of up to 50 m/s. This means an increase of 43% of the cutting speed which can be interrupted with this device, compared with previously used devices [44,45,49,50].…”
Section: Quick-stop Devicementioning
confidence: 84%
“…However, no systematic studies were carried out [48]. Recently developed quick-stop devices enable a reliable interruption of the grinding processes with cutting speeds of up to 35 m/s [44,45,49,50].…”
Section: State Of the Artmentioning
confidence: 99%
“…Therefore the quick stop device needs to accelerate the samples above the speed of the grinding wheel v c , which ranges from about 15 m/s up to 35 m/s for conventional grinding wheels. Calculation and high speed measurements of the acceleration velocity showed that a captive bolt pistol supplies enough energy to properly interrupt a grinding process [19]. The final device was fixed into a Blohm grinding machine and is shown in Fig.…”
Section: 3mentioning
confidence: 99%
“…In the same context and to obtain the chip attached to the workpiece for the investigation of chip formation processes in various machine tools, many other QSDs have been invented and employed by other researchers for various types of machining operations. For instance, in shaping, an electromagnetic QSD was fabricated by Wu et al 20 Griffiths 21 invented a QSD for deep drilling, however, in grinding readers are referred to the research works of G€ ottsching et al 22 and Ghosh et al 23 Readers are referred also to other more recent research works dealing with designing and manufacturing of new QSDs and the study of chip formation for various workpiece materials. For instance, Computer Aided Quick Stop Device (CAQSD) employing a servo motor is developed by Ozturk et al 24 for the study of dead metal zone formation in brass workpiece material.…”
Section: Introductionmentioning
confidence: 99%
“…20 Griffiths 21 invented a QSD for deep drilling, however, in grinding readers are referred to the research works of Göttsching et al. 22 and Ghosh et al. 23…”
Section: Introductionmentioning
confidence: 99%